Analysis of the Influence of High - Tech industry Agglomeration on Sulfur Dioxide Emissions in Yangtze River Delta - Gong, Junxi; Zhang, Cheng (Journal of Theory and Practice of Social Science, 2024)
This article mainly studies the impact of high-tech industry agglomeration on sulfur dioxide emissions in the Yangtze River Delta region. By establishing an index system, it is found that the development level of high-tech industry in different regions of the Yangtze River Delta is obviously different, among which Anhui province has the lowest level , and Shanghai and Jiangsu province have the highest level . In further empirical analysis, this paper uses panel data regression analysis, found that the high-tech industry agglomeration level of sulfur dioxide emissions have influences on inverted "U" type, namely with the improvement of agglomeration level, sulfur dioxide emission levels fall after rise, and in recent years, the population is not the key factors influencing the sulfur dioxide emission levels in Yangtze river delta, The secondary industry is still an important factor affecting sulfur dioxide emissions.